Evaluation of the Processes and Outcomes of a Physician Leadership Program: The Continuous Feedback Loop Design. Issue 4 (14th June 2022) - Gascon, Gregg M.; Chen, Huey T.; Morosanu, Liliana; Chen, Victor H.; Cass, Phil; Falcone, Robert
Abstract : Introduction: Physicians assume leadership roles in their health care organizations and practices often without support or training. The Physicians Leadership Academy provides integrated leadership seminars, mindfulness training, and executive coaching in a 10-month curriculum to physicians across area organizations. Methods: Program evaluators responded to stakeholders' need for continuous program improvement by developing a continuous feedback loop evaluation design incorporating a program monitoring system and a theory-driven program evaluation. Given the size of the 2019 to 20 cohort ( n = 19), a one-group pretest/posttest design was used to assess the mechanisms of the program (mindfulness and wellbeing) along with knowledge development, emotional intelligence, and personal and professional growth. The assessments used a combination of published and administrator-developed assessments to address the unique aspects of the program. Doing such ensured continuous improvement and sustainability for the program. Results: The cohort of physicians demonstrated significant engagement and learning across the curriculum, improved mindfulness, and improved capacity of the providers to affect their health care system and communities. Conclusions: The utility of the program was demonstrated through quantitative and qualitative analyses. Implications of the methodology for future evaluations of program developments are discussed.